Is Kimura's disease associated with juvenile temporal arteritis? A case report and literature review of all juvenile temporal arteritis cases. (2nd January 2021) - Tomizuka, Takafumi; Kikuchi, Hirotoshi; Asako, Kurumi; Tsukui, Daisuke; Kimura, Yoshitaka; Kikuchi, Yoshinao; Sasajima, Yuko; Kono, Hajime
Abstract: Both juvenile temporal arteritis (JTA) and Kimura's disease are eosinophilic inflammatory conditions but exhibit different clinical manifestations. Here, we describe a case involving a 40-year-old man who developed JTA secondary to Kimura's disease. Approximately 3 years before admission, masses appeared on both posterior auricles. A biopsy of the right posterior auricle mass led to a diagnosis of Kimura's disease. Approximately 4 months before admission, both masses increased in size, and almost simultaneously, the left temporal artery became distended. Histopathology of a biopsy of the left temporal artery revealed inflammatory findings with marked eosinophil infiltration and significant intimal hyperplasia with stenosis of the vascular lumen, indicating JTA. An analysis of the 48 reported cases of JTA, identified in a literature review, and the present case, revealed that Kimura's disease was detected in 6 cases, all of which involved Asians. In conclusion, this case and the literature review suggest that JTA can be accompanied by another eosinophilic inflammation-based disorder, Kimura's disease, particularly in Asians. This newly highlighted relationship between JTA and Kimura's disease could lead to a better understanding of JTA, which is an extremely rare disease.